Karakterisasi Metarhizium Anisopliae Yang Diformulasikan Dengan Enkapsulasi Sodium Alginat - Abdullah Al Halimir Rosyid (Fakultas Pertanian, 2026)
Metarhizium anisopliae is an entomopathogenic fungus with potential as a biological control agent for agricultural pests; however, the viability of its conidia can decline due to environmental factors, necessitating a formulation capable of providing protection. This study aimed to determine the effect of various concentrations of sodium alginate on the characterization and growth of M. anisopliae. The study was conducted at the Agroecotechnology Laboratory, Faculty of Agriculture, University of Jember, using a non-factorial completely randomized design (CRD) with four treatments: control, 2%, 3%, and 4% sodium alginate, each replicated five times. Encapsulation was performed using the ionotropic gelation method with a CaCl₂ solution. The parameters observed included the characteristics of the solid hydrogel resulting from encapsulation, colony diameter, and colony growth on Potato Sugar Extract (EKG) medium. The data were analyzed using ANOVA and Duncan’s test at the 5% significance level. The results showed that sodium alginate encapsulation successfully produced a stable solid hydrogel capable of preserving the morphological characteristics of M. anisopliae. The concentration of sodium alginate had a significant effect on colony diameter on day 14 (p < 0.05), with the highest colony diameter observed in the control (28.20 mm), while the 2%, 3%, and 4% sodium alginate treatments measured 23.12 mm, 22.95 mm, and 22.38 mm, respectively. Although colony growth in the encapsulation treatments was lower than in the control, all treatments still exhibited normal growth and sporulation. Thus, sodium alginate is not toxic to M. anisopliae and has the potential to be used as an encapsulation material to protect conidia in the development of bioinsecticide formulations.
Validasi dan Finalisasi Ratna 2 Juli 2026
Keywords: Metarhizium anisopliae; Enkapsulasi; Karakterisasi; Sodium Alginat; Agen Biokontrol